The Longitudinal Study of Australian Children Annual Statistical Report 2012 - Hancock, Kirsten J; Edwards, Ben; Zubrick, Stephen R (Australian Institute of Family Studies, 2013)
This chapter explores the impact of generational disadvantage on children, using data from 'Growing Up in Australia, the Longitudinal Study of Australian Children' (LSAC). It examines the effects of persistent disadvantage over two generations on children's wellbeing and development, and how these effects compare to children with just one generation of disadvantage, or no history of disadvantage at all. Family joblessness and parental divorce or separation are used as measures of disadvantage in this chapter. Topics include: parents' childhood experiences of growing up with family joblessness or separation; continuity of family joblessness and separation across generations; and child social-emotional problems and academic performance when their family has two generations of disadvantage, compared to children with disadvantage only in their parents' generation, only in their grandparents' generation, or no history of disadvantage at all.
Echoes of disadvantage across the generations? The influence of long-term joblessness and separation of grandparents on grandchildren
Keywords: Intergenerational Transfer; Employment -- Unemployment; Families -- Formation and dissolution; Disadvantage; Child Development; Childhood and child development; Intergenerational transfer; Labour market; Child Development; Families; Employment; Disadvantage; Intergenerational Transfer; Unemployment; Formation and dissolution; Intergenerational transfer; Employment and unemployment; Childhood and child development